Skype for dummies - Abdulezer, Loren; Abdulezer, Susan; Dammond, Howard; Safari eBooks (Hoboken, N.J. : Wiley Pub., 2007)
"See how to use Skype for secure chats and connect SkypeOut and SkypeIN. Here's the fun and easy way (r) to understand all the hype about Skype and make this cool alternative communication system work for you! You'll get great advice about hardware, directions for downloading and installing Skype, ideas for using Skype in your business, and the lowdown on making Skype calls to people with old-fashioned phones"--Resource description page.
Description based on print version record.
Includes index.
Keywords: Internet telephony; Skype (Electronic resource); Broadband communication systems; Electronic books